2012
DOI: 10.5424/sjar/2012103-437-11
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake dynamics, yield and quality as influenced by nitrogen fertilization in ‘Piel de sapo’ melon

Abstract: The need to reduce nitrogen (N) fertilizer pollution strengthens the importance of improving the utilization efficiency of applied N to crops. This requires knowledge of crop N uptake characteristics and how fertilization management affects it. A three-year field experiment was conducted from May to September in central Spain to investigate the influence of different N rates, which ranged from 11 to 393 kg ha -1 , applied through drip irrigation, on the dynamics of N uptake, nitrogen use efficiency (NUE), frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…The FAO 56 Penman-Monteith method is recommended as the standard method for ET 0 estimation [29,30]. Fernández et al reported the FAO 56 Penman-Monteith equation with a fixed aerodynamic resistance of 295 s m −1 can better estimate daily ET 0 in greenhouse [31]:…”
Section: Irrigation Managementmentioning
confidence: 99%
“…The FAO 56 Penman-Monteith method is recommended as the standard method for ET 0 estimation [29,30]. Fernández et al reported the FAO 56 Penman-Monteith equation with a fixed aerodynamic resistance of 295 s m −1 can better estimate daily ET 0 in greenhouse [31]:…”
Section: Irrigation Managementmentioning
confidence: 99%
“…A number of studies have shown that nitrogen influences soluble solids content (Bhella and Wilcox, 1989). However, previous studies carried out under the same experimental conditions stated that total soluble solids were not affected by the application of N (Castellanos et al, 2011(Castellanos et al, , 2012. Welles and Buitelaar (1998) reported that LAI has an effect on fruit soluble solids by extending the fruit developing period resulting in an increase in total soluble solids for this crop…”
Section: Discussionmentioning
confidence: 79%
“…For the main part, melon is cultivated in zones vulnerable to nitrate pollution in the center of Spain (Directive 91/676/ EEC), where more than half of the total wine production of the country is concentrated (MAPAMA, 2013). Thus, the application of any amendment is of special interest to this area from both an economic and an environmental point of view, given the goal of securing maximum yield with minimum water and fertilizer consumption and minimum loss of N (Castellanos et al, 2012;Requejo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the application of nutrients should be optimized, considering the time and rate of absorption by crops A study conducted by Colla, Suárez and Cardarelli (2010) points out that the maximum total yield, marketable yield, number of fruits and fruit weight for the melon crop were obtained with the use of 120 kg ha -1 of N applied through fertigation. Castellanos et al (2012) found maximum yield of Santa Claus melon with N application of 85 kg ha -1 through fertigation. Evaluating melon yield under conventional fertilization with N and K, Silva et al (2014) found maximum yield with N and K applications of 320 and 640 kg ha -1 , respectively.…”
Section: Introductionmentioning
confidence: 85%